The Antiinfluenza Virus Activity of Hydroalcoholic Extract of Olive Leaves: Antiviral activity of olive leave extract - Moatari, Afagh; Nekooeian, Ali Akbar; Motamedifard, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2006)
The influenza viruses are major etiologic agents of human respiratory infections, and inflict a sizable health and economic burden. This study examines the antiinfluenza virus activity of hydroalcoholic extract of olive leaves (OLHE). Olive leaves were collected from gardens around the city of Shiraz, characterized, dried, ground to powder, and its hydroalcoholic extract was prepared. The influenza viruses were isolated from patients and characterized by standard antiinfluenza sera. Virucidal effects of OLHE (10-1 to 103 μg/ml) were examined in pretreatment, treatment and incubation protocols using quantal assay after incubation for 72 h. All experiments were performed three times in quadruplicates. Pretreatment of the cell line with OLHE for one hour followed by the addition of the virus was associated with virucidal effects (1 to 1000 μg/ml). OLHE added one hour after incubation of the virus with cell did not show antiviral effects. OLHE incubated with the virus for one hour, and then added to the cell line did have antiviral activity (1 to 1000 μg/ml). The findings indicate that antiviral activity of OLHE occurred extracellularly, probably by changing the properties of membrane of the virus, rather than that of the cell, to prevent the virus from attaching and penetrating the cell line.